THE ENHANCEMENT OF ORGANIZATION CITIZENSHIP BEHAVIOR OF A TEACHER BY STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICATION - Setyaningsih, Sri; ., Naziroh (UNIVERSITAS PAKUAN, 2020)
The success and sustainability of an organization is largely determined by the willingness of employees to behave well not only when doing their main tasks, but also the extra behavior of wanting to be good employees. However, there are indications that teachers at MTs Negeri Jakarta Timur only perform basic tasks and do not show behaviors that support organizational effectiveness outside of this. The purpose of this study is to determine the relationship between Transformational Leadership and Self-Efficacy on Organizational Citizenship Behavior either partially or collectively. The population in this study were MTSn teachers in the East Jakarta area with a sample of 243 respondents consisting of 18 MTSn in the East Jakarta area. Data collection was carried out by distributing questionnaires and data processing was carried out by simple regression analysis and multiple regression analysis. The results showed that (1) Transformational leadership has a positive and significant relationship with teachers' Organizational Citizenship Behavior. (2) Self-efficacy has a positive relationship with teachers' Organizational Citizenship Behavior. (3) Transformational Leadership and Self-Efficacy together have a positive and significant relationship with teachers' Organizational Citizenship Behavior.